2018
DOI: 10.1093/schbul/sby142
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Deficits Predict Impaired Insight in Schizophrenia Across Symptom Profiles: A Latent Class Analysis

Abstract: The integrated model of insight in schizophrenia suggests that poor insight is the result of multiple factors which compromise persons' abilities to integrate streams of information into a personal awareness of psychiatric challenges, and make adaptive responses. This model hypothesizes that metacognitive deficits, or difficulties forming a complex and integrated understanding of the self and others, influence insight, regardless of other proximal causes including clinical profile. To explore this possibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 86 publications
(94 reference statements)
0
32
0
Order By: Relevance
“…Of note, to a large extent many contemporary approaches to metacognition, including Flavell's relatively later work (Flavell et al, 2002), emphasize the practical purposes of metacognitive knowledge and the self-regulatory aspects of metacognition. These components are evident in theoretical discussion of metacognition and the Lysaker et al (2018) review of different metacognitive approaches to the treatment of psychosis which treat metacognitive processes as having a regulatory function that allows person to doubt and subsequently decide upon different courses of action. One aspect of metacognition, however, that is often overlooked, is that metacognition is entwined with intersubjective experience.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, to a large extent many contemporary approaches to metacognition, including Flavell's relatively later work (Flavell et al, 2002), emphasize the practical purposes of metacognitive knowledge and the self-regulatory aspects of metacognition. These components are evident in theoretical discussion of metacognition and the Lysaker et al (2018) review of different metacognitive approaches to the treatment of psychosis which treat metacognitive processes as having a regulatory function that allows person to doubt and subsequently decide upon different courses of action. One aspect of metacognition, however, that is often overlooked, is that metacognition is entwined with intersubjective experience.…”
Section: Introductionmentioning
confidence: 99%
“…Moritz et al (2018) make a similar point that exercises designed to combat reasoning bias may also impact health when they enhance the capacity for self-reflection in the world. Others have suggested that diverse approaches, including psychodynamic and humanistic psychotherapy, might also promote health via their effects on metacognition (Knauss et al, 2018; Lysaker et al, 2019a).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of combined interventions on social functioning should also be explored. For example, metacognition, or the ability to form an integrated and complex understanding of the self and others, has been associated with social functioning and insight in psychotic disorders (Lysaker et al, 2019). No studies in this review incorporated metacognitive approaches, and addressing metacognition may lead to improved insight into cognitive impairments and treatment needs, thus promoting engagement in CTR interventions (Vohs et al, 2018).…”
Section: Discussionmentioning
confidence: 99%